Corporate Social Responsibility and Financial Performance: Moderating Role of Intellectual Capital - Achmad Iqbal; Sutrisno T; Roekhudin Roekhudin (Institute of Research and Community Service, University of Brawijaya)
This study aims to examine the impact of corporate social responsibility (CSR) on corporate performance in Indonesia and examine the role of intellectual capital as a moderating variable that can increase the influence of CSR on company performance. Hierarchical regression analysis is used to test the effect of CSR on performance and test intellectual capital as a moderating variable that can increase the influence of CSR on corporate performance. This study uses 147 samples of observation data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the year 2013-2015. The results showed that CSR has an effect on company performance as measured by Return on Asset (ROA). The higher CSR disclosures made by the company then can improve the company's performance (ROA). The results of this study also show that intellectual capital as a moderation variable is proven empirically able to increase the influence of CSR on company performance. These results indicate that the improvement of intellectual capital of the company including human capital, relational capital, and structural capital can increase the influence of CSR on company performance (ROA).